PEMETAAN SEBARAN DATA KURASI UKM/IKM BERBASIS QGIS DI PROVINSI BANTEN - Widyawati Widyawati; Reni Febriani; Dihan Ahmad Baslayn; Agung Sudrajad; Nely Hartika (LPPM Unbaja, 2023)
According to data from Dinas Koperasi dan UKM of Banten province, the number of UKM/IKM in Banten has reached three hundred (300) thousand which is spread across 5 (five) districts/cities. With such large number of UKM/IKM, one of the obstacles faced by decision makers (government) is the difficulty in classifying the distribution of UKM/IKM where without correct mapping it will be difficult for decision makers to provide guidance that can increase the economic growth of UKM/IKM. The results of this study are a Geographic Information System (GIS) which shows a mapping of the distribution of UKM/IKM in Banten province based on the type of business. From the results of the mapping it is concluded that UKM/IKM with culinary types are concentrated in the city centre of both Cilegon City and also Serang City while UKM/IKM with craft business are concentrated in the suburbs.